Identification of a novel mutation in a patient with pseudohypoparathyroidism type Ia - Ye Seung Lee; Hui Kwon Kim; Hye Rim Kim; Jong Yoon Lee; Joong Wan Choi; Eun Ju Bae; Phil Soo Oh; Won Il Park; Chang Seok Ki; Hong Jin Lee (Korean Pediatric Society, 2014)
Pseudohypoparathyroidism type Ia (PHP Ia) is a disorder characterized by multiform hormonal resistance including parathyroid hormone (PTH) resistance and Albright hereditary osteodystrophy (AHO). It is caused by heterozygous inactivating mutations within the Gs alpha-encoding GNAS exons. A 9-year-old boy presented with clinical and laboratory abnormalities including hypocalcemia, hyperphosphatemia, PTH resistance, multihormone resistance and AHO (round face, short stature, obesity, brachydactyly and osteoma cutis) which were typical of PHP Ia. He had a history of repeated convulsive episodes that started from the age of 2 months. A cranial computed tomography scan showed bilateral calcifications in the basal ganglia and his intelligence quotient testing indicated mild mental retardation. Family history revealed that the patient's maternal relatives, including his grandmother and 2 of his mother's siblings, had features suggestive of AHO. Sequencing of the GNAS gene of the patient identified a heterozygous nonsense mutation within exon 11 (c.637 C>T). The C>T transversion results in an amino acid substitution from Gln to stop codon at codon 213 (p.Gln213*). To our knowledge, this is a novel mutation in GNAS.